Formation of a preschooler's spiritual personality through the prism of Ukrainian pedagogy - Oresta Karpenko (Maria Curie-Skłodowska University, Lublin, Poland, 2018)
In the history of Ukrainian pedagogical thought, the problem of formation of a preschool child's spiritual personality is given special attention. There are different approaches to the study of concepts, content and principles of spirituality, the spiritual world of an individual, spiritual and moral values. Spiritual values and priorities of society arise from cultural and historical traditions, the experience of the nation. The content of such dissimilar categories as "spirituality" and "cordiality" has been studied. Spirituality expresses orientation of a human being toward the transcendent, whereas cordiality is defined by kindness in respect of people. Spiritual values are monitored and supported by public opinion and human conscience which helps normalize relations, brings order to and maintains harmony in society. The main task of educators is to instill moral self-awareness in every child and teach it spiritual values. Program requirements include promotion of spiritual ideas about the spiritual ideal, enrichment of emotional experience and formation of a certain self-attitude. Formation of spiritual basics must begin in the first years of life. In preschools, components of spiritual education are implemented through various forms of educational work.